KESTABILAN SISTEM PREDATOR-PREY LESLIE - Dewi Purnamasari; Faisal Faisal; Aisjah Juliani Noor (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2009)
Mathematical models are commonly used to describe physical and nonphysicalphenomena which appeared in the real world. Generally speaking, theapplication of mathematical models is usually formed into a differential equationsystem. For example, Predator-Prey Leslie system is one mathematical model ofnon-linier differential equation system which has been introduced by Leslie(1948). This system describes an interaction model between two populationswhich contain two equations as follows :ax bx cyxdtdx  dy 2 where a, b, c, e and f are positive constants.In the Predator-Prey Leslie system, the relationship between each variablein the interaction process between prey and preadtor is dependend and influencedby changing value of system. Therefore, this will effect to the stability system.The method of this research is a study of literature from relevant booksand journals. To obtain a stability system, the stability poits of a system have to befound firest, then continue with linierization. From this, it will obtainedcharacteristic roots or eigen values. These values will show a stable state atsystem equilibrium points.As a result, it is found that Predator-Prey Leslie system, in this case,reaches a stability at equilibrium point K2, but not the case at K1.